Recurrent Ameloblastoma in the Free Fibula Flap: Review of Literature and an Unusual Case Report - Basat, Salih Onur (J Maxillofac Oral Surg, 2015)
Ameloblastoma is the second most common odontogenic tumor of the oral cavity with the primary site being the mandible. The ratio of maxillomandibular involvement however is 5:1 in favor of the mandible. The most common complaint is a painless swelling over the mandibular area. Despite its benign nature, ameloblastoma has a high local recurrence rate, with the most recurrences seen within 5 years after operation. Biopsy and radiological evaluation may be helpful in differentiating the subtypes of ameloblastoma. Differentiation is important because some subtypes are more aggressive than the others. Preoperative planning may be done according to this classification, which can help decrease the recurrence rate. In our case, a 26-year-old female patient with recurrent ameloblastoma which developed on the fibular flap is presented. The free fibular flap and the left parasymphyseal part of the mandible were totally excised. Ameloblastoma was confirmed on pathological examination. We reconstructed the left mandibular site with a reconstruction plate and recurrence was not seen during follow up period.